The work of physical education professionals in Family Health Support Centers (NASF): a national survey - Santos, Sueyla Ferreira Da Silva Dos; Benedetti, Tânia R. Bertoldo; Medeiros, Tiago Francelino; Freitas, Cintia De La Rocha; Sousa, Thiago Ferreira E; Costa, José Luiz Riani [UNESP] (Universidade Federal de Santa Catarina, 2015)
This is a descriptive and quantitative national survey aimed at presenting Health Education practices (HE) developed by Physical Education professionals working at NASF in Brazil. Overall, 296 professionals participated in this study, stratified by Brazilian regions and NASF groupings. Electronic interviews were conducted regarding the activities developed at the unity where each NASF professional worked. The main activities reported were gymnastics (40.1%), and walking (29.4%), having as their priority public elderly people (68.8%), groups of hypertensive and diabetic patients (30.9%) and young people (48.3%), respectively. The most discussed topics in lectures and orientations was the importance of physical activity (51.4%) and the second most cited was the prevention/treatment of comorbities (32.3%). The community spaces most utilized by Physical Education professionals to develop activities were: public squares, community centers and schools in the southeastern and southern regions of Brazil, and religious entities in the northeastern and Midwestern regions. In conclusion, in spite of the diversity of activities developed in different regions of Brazil, there is predominance of traditional Physical Education contents, which reflect the need of permanent education of such professionals to improve the quality of services offered to the community.

Estudo de levantamento nacional descritivo e quantitativo que visa apresentar as práticas de Educação em Saúde (ES) desenvolvidas pelos Profissionais de Educação Física do NASF no Brasil. Participou uma amostra representativa de 296 profissionais, estratificada pelas regiões brasileiras e modalidades de NASF. Foi realizada uma entrevista telefônica sobre a caracterização das atividades de ES desenvolvidas no NASF nas quais o profissional atuava. As principais atividades referidas foram ginástica (40,1%) e caminhada (29,4%), tendo como público participante prioritário os idosos (68,8%), grupos de hipertensos e diabéticos (30,9%) e os jovens (48,3%), respectivamente. O primeiro tema mais abordado nas palestras e orientações em saúde foi sobre a importância da atividade física (51,4%) e o segundo mais citado foi prevenção/tratamento de comorbidades (32,3%). Os espaços comunitários mais utilizados pelo Profissional de Educação Física, além da Unidade de Saúde da Família, para realização das atividades de ES foram: praças, centros comunitários e escolas, nas regiões Sudeste e Sul, e entidades religiosas no Nordeste e Centro-Oeste. Conclui-se que, apesar da diversidade das ações promovidas nas diferentes regiões do Brasil, há uma predominância de atividades baseadas nos conteúdos tradicionais da Educação Física, refletindo a necessidade de educação permanente dos profissionais para potencializar a oferta de serviços à comunidade.
Atuação do profissional de Educação Física nos Núcleos de Apoio à Saúde da Família: um levantamento nacional
Keywords: Brazil; Family health; Health education; Physical education and training; Brasil; Educação em saúde; Educação física e treinamento; Saúde da família